OPTIMIZATION METHOD OF CYCLOIDAL PIN GEAR TOOTH PROFILE CURVE BASED ON PRESSURE ANGLE - LI YouTang; DONG HaoNan (Jixie qiangdu, 2024)
According to the theory of cycloidal pin gear drive,a method of tooth profile optimization based on pressure angle was proposed.The cycloidal pin gear tooth profile was divided into working section and non⁃working section.The factors that affected the pressure angle of the working section were modification parameters and design parameters.The influence of the two types of parameters on the pressure angle was discussed.With the two types of parameters as design variables and the average pressure angle of the working section as the objective function,the cycloidal gear of RV⁃550E reducer was optimally designed by determining the boundary conditions from the requirements of motion and lubrication.The results show that this method reduces the average pressure angle of the working section of the example by 4.14%,the maximum value of the pressure angle in the single tooth meshing process by 1.35%,the maximum Mises stress of the contact tooth pair before and after optimization by 20.77%,the occurrence position is transferred from the cycloidal gear to the pin gear,and the model mass reduces by 9.38%,which can ensure that there is no undercut phenomenon and obtain a good combined modify effect.